Apakah Good Corporate Governance Mampu Memperkuat Kinerja Bank Umum Syariah di Indonesia? - Sri Lestari Kurniawati; Linda Purnama Sari; Zubaidah Nasution (Department of Islamic Banking, 2021)
This study aims is to analyze non-performing financing and liquidity on the profitability of Islamic Commercial Banks in Indonesia with good corporate governance as a moderating variable. This study uses the variable Profitability (ROA) as the dependent variable, non-performing financing (NPF) and liquidity (FDR), as the independent variable and Good Corporate Governance (Independent Commissioner) as the moderating variable. The sampling method used purposive sampling in order to obtain 12 BUS with a research period of 2010-2019. The analysis technique used is statistical analysis of panel data with eviews 8.0. The results of the study stated that NPF had a significant negative effect on profitability, FDR had a significant positive effect on profitability. GCG as a moderating variable strengthens the influence of NPF on profitability, while GCG is not a moderating variable of the effect of FDR on profitability. The conclusion is that GCG is only a moderating variable of the effect of NPF on profitability.